PRÁTICAS PEDAGÓGICAS COLABORATIVAS NA ALFABETIZAÇÃO DO ALUNO COM TRANSTORNO DO ESPECTRO AUTISTA - Vera Lucia Messias Fialho Capellini; Priscila Hikaru Shibukawa Shibukawa; Simone Catarina de Oliveira Rinaldo (Universidade do Oeste Paulista, 2016)
The appropriation of the writing system by students with Autistic Spectrum Disorder (ASD) is a way to facilitate their communication, peculiar difficulty disorder. This study aimed to investigate and describe the literacy process of a student with ASD inserted into a common class of mainstream education, observing the strategies used by the teacher in the literacy process and collaborative support. They participated in the study, a teacher and a student with Autism Spectrum Disorder a public school in São Paulo. For data collection was used the observational technique and initial and final interview with the teacher. The results show the difficulty in performing interventions collaboratively. However, it could be seen a breakthrough in the development of written language by autistic student. It concludes that the credibility on student learning with ASD is the first step in its literacy and literacy, requiring collaborative work between special education and regular education.